HXE 224 - Critical Theory And Practice June 2016 - PPIK, Pusat Pengajian Ilmu Kemanusiaan (Universiti Sains Malaysia, 2016)
Please check that this examination paper consists of THREE pages of printed material before you begin the examination. Answer THREE questions. Answer ONE question from Section A, ONE from Section B and ONE more from either Section A or B.